Social participation and health: a collaborative experience on chronic kidney disease - Francisco J Mercado-Martínez; Paulina Madrigal-Vargas; Carlos E Sánchez-Pimienta (Instituto Nacional de Salud Pública, 2018)
Objective. To identify challenges derived from renal insufficiency, as well as potential solutions and an agenda for action. Materials and methods. By adopting a collaborative research approach, diverse stakeholders -sick people, family members, advocacy groups, health professionals, and academics- participated in two gatherings in the context of the World Kidney Day in Guadalajara, Mexico and created an agenda for action. Data was gathered through group discussions. Results. Two main issues are faced by kidney sick people and their family members: the first one related with health services and, second, the lack of economic resources to pay for renal treatment. The agenda for action included rallying on public squares, installing day of the dead altars, video making, and publishing a book. Conclusion. Participation of diverse stakeholders is a valuable option to face challenges derived from renal insufficiency.